A Comparative Study of the Performance of Finned Tube Air Cooled Condenser with Refrigerants R22 and R407C - Imran, Ahmed Abdulnabi; Hatem, Falah Fakhir; Hadi, Faeza Mehdi (Al-Nahrain Journal for Engineering Sciences, 2017)
Mathematical and numerical study of finned tube air cooled condenser for air conditioning unit with two ton refrigeration capacity using R22 as a base fluid and R407C an alternative fluid was investigated. Different parameters were considered in this work, such as condensing pressure, ambient temperature and refrigerant mass flow. A comparison of performance between two condensers when using R22 and R407C were performed. A redesign the condenser operates with the R407C to operate with the same system that operates with R22. The result showed the same behavior for the two refrigerants, the condensers are possible to work with R407C for the same geometry and some modifications in the structure of heat exchange with the same air velocity. The proposed model was validated with the outputs from the test data given in literature papers, derived from air cooled condensers with different dimensions. The results exhibited an agreement with the experimental results with a percentage of compatibility ± 10%.